2020
DOI: 10.1080/20477724.2020.1850982
|View full text |Cite
|
Sign up to set email alerts
|

Why are Asian countries outperforming the Western world in controlling COVID-19 pandemic?

Abstract: COVID-19 already caused more than 1,260,000 deaths around the world. However, mortality rates are not equal amongst the different countries. Mortality rates are ranging from less than 1 death per million in Taiwan, Vietnam and Thailand to 1,112 deaths per million in Belgium. In the present article, we report a striking difference in mean per million mortality between Asian and European countries (2.7 vs 197 deaths per million population, p < 0.001). In addition, we confirmed that the later a specific country w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 6 publications
0
18
0
3
Order By: Relevance
“…Furthermore, until early 2020, people in most areas of the world were not accustomed to wearing face masks. Consequently, the acceptance of wearing masks was low in Europe at the beginning of the pandemic, which stands in stark contrast to the commonly high usage rates in various Asian communities (see Landoni et al., 2021 ; MacIntyre & Chughtai, 2015 ; van der Sande et al., 2008 ). Research has recently identified some concrete factors related to personality traits that contribute to explaining individual mask-wearing behaviour.…”
mentioning
confidence: 90%
“…Furthermore, until early 2020, people in most areas of the world were not accustomed to wearing face masks. Consequently, the acceptance of wearing masks was low in Europe at the beginning of the pandemic, which stands in stark contrast to the commonly high usage rates in various Asian communities (see Landoni et al., 2021 ; MacIntyre & Chughtai, 2015 ; van der Sande et al., 2008 ). Research has recently identified some concrete factors related to personality traits that contribute to explaining individual mask-wearing behaviour.…”
mentioning
confidence: 90%
“… 20 We set the age cut- off at >52 years, which is significantly lower than the one usually found in literature (>65), 21 , 22 this can be attributed to the specific SARS-CoV-2 virus characteristics and to the impact of environmental factors in different countries. 23 The surprising findings of female sex being a predictor of poor outcome in terms of the physical component of QoL might be, at least in part, a consequence of the drawbacks of the SF-36 scale itself. Some aspects related to physical activity are a priori easier to perform for men than for women, and this could lead to an underestimation of the physical component of QoL in females.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, the world has struggled to adapt and mitigate the impact of a virus that is proving to be highly adaptable and difficult to eradicate. This is especially felt in Asia, where it is now the new epicenter of COVID-19 with the highest cumulative number of notice in the event of a new pandemic [2]. Finally, wearing masks in many Asian countries is considered acceptable even during non-pandemics, and Asian societies are generally more willing to adhere to social distancing measures to prevent the further spread of COVID-19 [2].…”
Section: Introductionmentioning
confidence: 99%
“…Although this observation has not been systematically analyzed in detail, it can be postulated that the lower death rates from COVID-19 in Asia may be attributed to a younger population, which, as a result, has fewer comorbidities and is more likely to experience less severe COVID-19 [ 2 ]. Furthermore, many Asian countries have developed pandemic response systems that could be activated at short notice in the event of a new pandemic [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation